THE REPRESENTATION OF GENDER IDEOLOGY IN INDONESIAN TEXTBOOKS - Siti Cholisotul Hamidah (Jurusan Sastra Indonesia, 2017)
This research seeks to examine issues related to the representation of gender ideology in learning topics entailed in Indonesian textbooks. This research is a qualitative research employing gender theory and van Djik’s model of discourse analysis. The data encompassed topics discovered in units of texts in the Indonesian textbooks for Elementary, Junior High, and High School level, particularly in the components of the learning materials that include explanation (theoretical), examples, exercises, and tasks both in the language aspect as well as the literary work. 36 textbooks were successfully collected as the main data in which 3 books were obtained from each class for each level. Documentation was employed as the main data collection technique and the researcher played a role as the main instrument. The data were analyzed by using van Djik’s model of critical discourse analysis as well as the perspective of gender analysis. The results of the study on the gender representation in the textbooks were manifested in three forms, namely, (1) gender identity, (2) gender role, and (3) gender status. With regard to those three components, some points are worth-highlighting: (1) there are dichotomous differences between men and women, (2) there are some misinterpretations of marginalization particularly of women, and (3) gender polarization is also evident. Such conditions were resulted from the authors’ mental awareness, for they are influenced by the discourse in the society where they live in which discrimination towards women and domination of men are prevalent and continuously produced.